Peningkatkan Kualitas Pendidikan Keagamaan TPQ Nur ‘Ilmi Desa Karangpatihan - Ahmad Khoirudin; Ibnu Muchlis (Institut Agama Islam Sunan Giri Ponorogo, 2023)
Community service activities carried out by KPM Students of the Sunan Giri Ponorogo Islamic Institute which were carried out on July 3 - August 3 2023, located in Karangpatihan Village, Kec. Pulung Kab. Ponorogo has a very significant influence on the community, especially in the Karangpatihan village area, Kec. Pulung Kab. Ponorogo. Students received a very good welcome and high enthusiasm. With learning to recite the Koran as well as tutoring, the quality of religion and TPQ education for children in Karangpatihan village will improve. The supporting factors in these activities include: The community and children have a great willingness to obtain information and knowledge regarding improving the quality of Religious Education in Karangpatihan Village. The implementation of this community service uses the Asset Based Community Development ( ABCD ) method. The ABCD method is an approach to community empowerment by focusing on the assets owned by the community. The ABCD method focuses more on the content or potential and strength of a particular community, this asset does not matter how little it is in the community. ABCD assets are an invaluable resource to move towards improving lives